TABULA RASA AND THE DOGMAS OF RELIGIOUS EDUCATION - Ikhwansyah, Muhammad Fuad; Hunainah, Hunainah (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Humans as thinking creatures produce theories of thought. One of the well-known in the world of education is John Locke's Tabula Rasa theory. Religion is present as something that is believed by the Creator so both are two interesting things to study. The research method used is the literature by finding sources that are by following per under the discussion. The result of the discussion is that John Locke's Tabula Rasa theory that humans are born clean like white paper is not by following religious education. Because religions have innate beliefs that are innate, including Islam in the form of potential reason and conscience and the concept of nature, Christianity in the form of inherited sin, free will, and divine response, and Hinduism in the form of  Atman  or  atma , reincarnation, and  triguna . Nevertheless, the three religions still encourage humans to continue sense to gain knowledge and experience.